Hepatic and cardiac and iron overload detected by T2* magnetic resonance (MRI) in patients with myelodisplastic syndrome: A cross-sectional study. (January 2019) - Mantovani, L.F.; Santos, F.P.S.; Perini, G.F.; Nascimento, C.M.B.; Silva, L.P.; Wroclawski, C.K.; Esposito, B.P.; Ribeiro, M.S.S.; Velloso, E.D.R.P.; Nomura, C.H.; Kay, F.U.; Baroni, R.H.; et al.
Highlights: We evaluated organ iron overload in patients with myelodysplastic syndrome (MDS). Patients with hepatic iron overload had lower survival rates. Hepatic iron overload is detected by MRI before laboratory signs. Abstract: Introduction: Transfusion-dependent anemia and iron overload are associatedwith reduced survival in myelodysplastic syndrome (MDS). This cross-sectional study aimed to evaluate the prevalence of hepatic and cardiac overload in patients with MDS as measured by T2* magnetic resonance imaging (MRI), and its correlation with survival. Methods: MDS or chronic myelomonocytic leukemia patients had iron overload evaluated by T2* MRI. HIO was considered when hepatic iron concentration ≥ 2 g/mg. Cardiac iron overload was considered with a T2*-value < 20 ms. Results: Among 71 patients analyzed, median hepatic iron concentration was 3.9 g/mg (range 0.9–16 g/mg), and 68%of patients had hepatic iron overload. Patients with hepatic iron overload had higher mean ferritin levels (1182 ng/mL versus 185 ng/mL, p < 0.0001), transferrin saturation (76% versus 34%, p < 0.0001) and lower survival rates. Median cardiac T2*value was 42 ms (range 19.7–70.1 ms), and only one patienthad a T2* value indicative of cardiac iron overload. Conclusions: Hepatic iron overload is found in two thirds of patients, even in cases without laboratory signs of iron overload. Hepatic iron overload by T2* MRI is associated with a decreased risk of survival in patients with MDS.